2003
DOI: 10.1016/s0741-5214(03)00340-9
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory aortic aneurysm is associated with increased incidence of autoimmune disease

Abstract: Except for longer operating time and more need for blood transfusions in the IAA group, use of hospital resources was similar after operations to treat IAA or noninflammatory AAA. The study findings indicate an association between IAA and autoimmune disease. This is in accordance with other reports that showed a genetic risk determinant mapped to the human leukocyte antigen (HLA) molecule in these patients. Further research is necessary to explore whether IAA might be a separate entity with a role of antigen b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(58 citation statements)
references
References 33 publications
3
54
1
Order By: Relevance
“…A recent case-control study that compared inflammatory and noninflammatory abdominal aortic aneurysms showed that IAAAs are more (6). Likewise, in a recent study, we found that in 7 (44%) of 16 cases CP was associated with other autoimmune conditions, namely ANCA-positive renal disease and autoimmune tyroiditis (7).…”
Section: Discussionsupporting
confidence: 62%
“…A recent case-control study that compared inflammatory and noninflammatory abdominal aortic aneurysms showed that IAAAs are more (6). Likewise, in a recent study, we found that in 7 (44%) of 16 cases CP was associated with other autoimmune conditions, namely ANCA-positive renal disease and autoimmune tyroiditis (7).…”
Section: Discussionsupporting
confidence: 62%
“…The described association with autoimmune disorders and the often observed beneficial response to immunosupressive treatment would further fit the proposed hypothesis (9,10).…”
Section: Introductionsupporting
confidence: 65%
“…An association between chronic periaortitis and HLA-DRB1*03, an allele linked to several autoimmune conditions, was recently noted (42). This might explain the simultaneous occurrence of autoimmune disorders (e.g., lupus erythematosus, Wegener's granulomatotis, polymyalgia rheumatica) in some patients with chronic periaortitis (9,10,16) and the often observed beneficial response to immunosuppressive treatment (13). One might speculate that in predisposed patients, an exaggerated and persistent inflammatory response with subsequent development of chronic periaortitis results from the same stimuli and mechanisms that are involved in atherosclerosis development per se.…”
Section: Discussionmentioning
confidence: 97%
“…As other investigators have also suggested, vascular inflammation may lower vessel wall resistance, causing increased susceptibility to the formation of aortic aneurysms in patients with inflammatory rheumatic disease (17)(18)(19)(20)(21).…”
Section: Discussionmentioning
confidence: 79%